1996
DOI: 10.1002/(sici)1098-2302(199611)29:7<577::aid-dev3>3.0.co;2-r
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of infants' visual responsiveness to facial expressions of emotion

Abstract: An extensive literature documents the infant's ability to recognize and discriminate a variety of facial expressions of emotion. However, little is known about the neural bases of this ability. To examine the neural processes that may underlie infants' responses to facial expressions, we recorded event-related potentials (ERPs) while 7-month-olds watched pictures of a happy face and a fearful face (Experiment 1) or an angry face and a fearful face (Experiment 2). In both experiments an early positive component… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

19
120
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 227 publications
(140 citation statements)
references
References 36 publications
19
120
1
Order By: Relevance
“…ERP studies in infants have demonstrated different patterns of ERP responses to happy and fearful faces in 7-month-olds (Nelson and de Haan, 1996;Leppänen et al, 2007). In addition, it was reported that angry faces elicited a larger Nc component than fearful faces, possibly related to increased attention to threat-relevant signals, in 7-month- Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…ERP studies in infants have demonstrated different patterns of ERP responses to happy and fearful faces in 7-month-olds (Nelson and de Haan, 1996;Leppänen et al, 2007). In addition, it was reported that angry faces elicited a larger Nc component than fearful faces, possibly related to increased attention to threat-relevant signals, in 7-month- Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Nelson and de Haan (1996) reported that different ERP components were evoked by happy and fearful facial expressions. That is, both early and late positive components were observed in response to happy faces, whereas only a negative component (Nc) was identified for fearful faces.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The ERPs of infants as young as 6 months of age show a relatively late and small N170 component in response to face images (de Haan, Pascalis, & Johnson, 2002;Nelson & de Haan, 1996) that is not affected by inversion as in older infants and adult subjects (de Haan et al, 2002). They show instead later ERP differences ($400 ms after stimulus onset) between not only upright and inverted faces (de Haan et al, 2002), but also between emotional expressions (e.g.…”
Section: Electrophysiological Indices Of Face Processingmentioning
confidence: 97%
“…They show instead later ERP differences ($400 ms after stimulus onset) between not only upright and inverted faces (de Haan et al, 2002), but also between emotional expressions (e.g. happy vs. fear; Nelson & de Haan, 1996) and between their mothers' and strangers' faces (de Haan & Nelson, 1997). ERP studies with older children have shown that the N170 responses to faces do not reach full maturity until adulthood, decreasing in amplitude, and occurring at earlier latencies throughout the child and adolescent years (Taylor, Batty, & Itier, 2004;Taylor, McCarthy, Saliba, & Degiovanni, 1999).…”
Section: Electrophysiological Indices Of Face Processingmentioning
confidence: 99%